2020
DOI: 10.1007/s10676-020-09565-9
|View full text |Cite
|
Sign up to set email alerts
|

Responsible innovation in synthetic biology in response to COVID-19: the role of data positionality

Abstract: Synthetic biology, as an engineering approach to biological systems, has the potential to disruptively innovate the development of vaccines, therapeutics, and diagnostics. Data accessibility and differences in data-usage capabilities are important factors in shaping this innovation landscape. In this paper, the data that underpin synthetic biology responses to the COVID-19 pandemic are analyzed as positional information goods—goods whose value depends on exclusivity. The positionality of biological data impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In international practice, a color classification has been established for the use of biotechnology methods in industry, reflecting the global scale of biotechnology penetration into the world economy [1]. The color classifier of innovations in the economy based on biotechnology is presented in the most popular areas of growth of the modern economy and its individual sectors: "white" -industrial production; "red" -medicine and pharmaceutical industry; "green" -agriculture, including veterinary medicine and animal husbandry; "gray" -the branch of natural resource and environmental protection, bioremediation (the use of living organisms for detoxification and reducing the concentration of pollutants); "blue"artificial cultivation and processing of aquatic organisms [2]. Such a wide coverage of biotechnologies in sectors of the national economy in the world today forces experts to talk about the formation of a bioeconomy.…”
Section: Resultsmentioning
confidence: 99%
“…In international practice, a color classification has been established for the use of biotechnology methods in industry, reflecting the global scale of biotechnology penetration into the world economy [1]. The color classifier of innovations in the economy based on biotechnology is presented in the most popular areas of growth of the modern economy and its individual sectors: "white" -industrial production; "red" -medicine and pharmaceutical industry; "green" -agriculture, including veterinary medicine and animal husbandry; "gray" -the branch of natural resource and environmental protection, bioremediation (the use of living organisms for detoxification and reducing the concentration of pollutants); "blue"artificial cultivation and processing of aquatic organisms [2]. Such a wide coverage of biotechnologies in sectors of the national economy in the world today forces experts to talk about the formation of a bioeconomy.…”
Section: Resultsmentioning
confidence: 99%
“…Risks emerge inherent to the adoption of technology in the surveillance of people's behavior and the exposure of their personal data (Bhatt et al, 2022). Furthermore, in Bruynseels (2021), it is further reported that access to data and differences in data usage capabilities are relevant ethical factors in the adoption of responsible innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, business and social organizations must face the challenges of sustainable development by collaborating with a wide range of stakeholders to conduct innovation aligned to with the “norms of doing good and avoiding harms.” In such a scenario, RI, has become a cutting‐edge research topic intensively discussed among global scholars, particularly after the Ebola and the COVID‐19 outbreaks (Arslan & Tarakci, 2020; Arthur & Owen, 2019; Bruynseels, 2020; Genus & Stirling, 2018; Steur et al, 2020; Voegtlin & Scherer, 2017; Waldron et al, 2020).…”
Section: Theoretical Foundationmentioning
confidence: 99%